Solving Geometry Problems by Alternative Methods in Mathematics Education (European Journal of Pure and Applied Mathematics, 2023)
Solving geometry problems is both difficult and interesting. Difficult because there is no general algorithm to solve more or less non-trivial problems as every single problem requires individual and creative approach. At the same time, this is a very interesting activity, because for almost every problem there are plenty of ways to solve it. In this work, we present the method of auxiliary circle divided into equal parts. This method allows finding solution algorithm for some geometry problems which are hard to solve by the method of additional constructions.
Keywords: geometry problem, Ceva’s theorem, regular polygon, solution algorithm